2015
DOI: 10.1111/pala.12185
|View full text |Cite
|
Sign up to set email alerts
|

InvestigatingDevonian trees as geo‐engineers of past climates: linking palaeosols to palaeobotany and experimental geobiology

Abstract: We present the rationale for a cross-disciplinary investigation addressing the 'Devonian plant hypothesis' which proposes that the evolutionary appearance of trees with deep, complex rooting systems represents one of the major biotic feedbacks on geochemical carbon cycling during the Phanerozoic. According to this hypothesis, trees have dramatically enhanced mineral weathering driving an increased flux of Ca 2+ to the oceans and, ultimately, a 90% decline in atmospheric CO 2 levels through the Palaeozoic. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 95 publications
2
49
0
Order By: Relevance
“…These changes have been linked to the colonization of terrestrial landscapes by rooted plants (1)(2)(3)(4)(5). Previous studies have emphasized the effects of early trees and forests, which first appeared in the Middle Devonian (6)(7)(8), on enhanced chemical weathering rates and soil development (2,(9)(10)(11). However, the roles that vascular plants played in soil production and landscape stability before the evolution of trees and deep roots (the interval from ∼420 to 390 Ma) are poorly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These changes have been linked to the colonization of terrestrial landscapes by rooted plants (1)(2)(3)(4)(5). Previous studies have emphasized the effects of early trees and forests, which first appeared in the Middle Devonian (6)(7)(8), on enhanced chemical weathering rates and soil development (2,(9)(10)(11). However, the roles that vascular plants played in soil production and landscape stability before the evolution of trees and deep roots (the interval from ∼420 to 390 Ma) are poorly understood.…”
mentioning
confidence: 99%
“…Some species have been recorded as bearing shallow rooting systems (or root-like structures) (16)(17)(18)(19)(20), others as having surficial or shallowly subterranean rhizomatous axes with rhizoids (21)(22)(23). Thus, the geochemical effect of these plants on the substrate (or soils) was presumably limited (11), and their capacity for landscape stabilization was trivial. However, because of a poor fossil record, it remains quite unclear how the "hidden half" ecosystem (24), with buried structures growing in soils, functioned during the early stage of vascular plant radiation.…”
mentioning
confidence: 99%
“…Roots and mycorrhizal symbionts are thought to have a major impact on biogeochemical cycles (Taylor et al ., ); however, estimating the magnitude of these effects in the earliest forests is challenging. Experiments using extant mycorrhizal trees as analogues of past forests have been performed under elevated CO 2 atmosphere conditions approximating those of the middle Devonian (Morris et al ., ). This has demonstrated that under elevated atmospheric CO 2 , trees support larger hyphal networks and AM fungi increase physical alteration of silicate mineral surfaces (Quirk et al ., ).…”
Section: Limits Of Paleontological Vs Genetic Approaches and Perspectmentioning
confidence: 97%
“…In contrast to the wealth of information from plants with rhizoid‐based rooting systems from the Rhynie chert, knowledge of fungal symbioses associated with the primitive roots remains surprisingly limited. Nothing is known about fungal mycorrhizal symbionts in the rooting systems of the trees in the earliest forests of the Mid and Late Devonian (398–359 million yr ago (Ma); Morris et al ., ). These forests were formed by Cladoxylales (an extinct group of uncertain affinities, reproducing by spores) (Xu et al ., ) and progymnosperms, (a group of plants reproducing by spores but with secondary growth of the vascular tissues similar to true gymnosperms; Figs , ).…”
Section: From Early Land Plants To Early Trees: the Origin Of Roots Amentioning
confidence: 99%
See 1 more Smart Citation